Specific features of amoxicillin‐associated Drug Reaction with Eosinophilia and Systemic Symptoms syndrome: a nationwide study. (13th September 2021) - Largeau, B.; Agier, M.‐S.; Beau‐Salinas, F.; Pariente, A.; Maruani, A.; Vial, T.; Jonville‐Béra, A.‐P.
Abstract: Background: Growing evidence indicates that amoxicillin induces herpesvirus replication in vitro . As these play a central pathophysiological role in Drug Reaction with Eosinophilia and Systemic Symptoms syndrome (DRESS), amoxicillin could present with specific DRESS features. Objective: To characterize the onset patterns of amoxicillin‐associated DRESS. Methods: All cases of DRESS (Kardaun score ≥4) involving amoxicillin and reported in the French Pharmacovigilance Database between January 1, 2004 and November 30, 2019 were included. Onset circumstances for these cases were categorized considering the onset delay from amoxicillin initiation, and the presence of concomitant medications with a compatible time to onset. Results: A total of 146 probable cases or definite cases of DRESS were included. Three onset circumstances were identified: (i) 'amoxicillin clear culprit' where amoxicillin was the sole suspect drug or when concomitant drugs of compatible time to onset were not reported to cause DRESS ( n  = 62); (ii) 'amoxicillin possible culprit' in the presence of other potentially culprit drugs in addition to amoxicillin ( n  = 44) and (iii) 'flare' where amoxicillin, used after DRESS onset, induced flare‐up reactions ( n  = 40). The median time to onset was 5 days (IQR 2–11) in 'clear culprit', and 18 days (IQR 7–26) in 'possible culprit' cases. In 'flare' cases, the median latency between amoxicillin initiation and flare‐up reactions was 3 days (IQR 2–5). Conclusions: Amoxicillin can induce DRESS with a specific early onset and exacerbate DRESS from another drug.